Diagnosis and Management of Head and Face Pain A Practical Approach (Springer International Publishing, 2018)
This text is a comprehensive guide to the evaluation of patients with head and face pain. It is a resource for any physician or dentist to properly diagnosis and to learn the options for treating head and face pain, as well as know when to refer a patient to a specialist and how to identify which specialist is needed. It discusses the basic anatomy, etiology, and pathophysiology of head and face pain, classification guidelines for treatment, and clinical case examples. Additional chapters on nerve blocks, nerve stimulators, radiosurgery, microvascular decompression, Botox, and alternative and complementary medicine are also included. Diagnosis and Management of Head and Face Pain will be an invaluable resource for otolaryngologists, family physicians, oral surgeons, dentists, neurologists, neurosurgeons, pain specialists, and patients who suffer from head and face pain.